Finite-Size Scaling for Potts Models - Borgs, Christian; Kotecky, Roman; Miracle-Sole, Salvador (J. Stat. Phys., 1990)
Recently, two of the authors (C.B. and R.K.) developed a rigorous theory of finite-size effects near first-order phase transitions.